Răspuns :
a + b = 123
a + 83 = (b + 49) * 2
a + 83 = 2b + 98
a = 123 - b
123 - b + 83 - 2b = 98
- 3b = - 123 - 83 + 98
- 3b = - 108
b = 108 : 3
b = 36
a = 123 - 36
a = 87
a + 83 = (b + 49) * 2
a + 83 = 2b + 98
a = 123 - b
123 - b + 83 - 2b = 98
- 3b = - 123 - 83 + 98
- 3b = - 108
b = 108 : 3
b = 36
a = 123 - 36
a = 87
a |----------|----------|83|
b |----------|49| } 123.
123 + (83+49)= 123+ 132=255 ( 3 segmente egale)
255 : 3 = 85 (un segment)
2 × 85 - 83 = 87 (a)
85 - 49 = 36 (b)
Proba : 87 + 36 = 123 (a+b).
b |----------|49| } 123.
123 + (83+49)= 123+ 132=255 ( 3 segmente egale)
255 : 3 = 85 (un segment)
2 × 85 - 83 = 87 (a)
85 - 49 = 36 (b)
Proba : 87 + 36 = 123 (a+b).